Dampak Kekuasaan, Antara Hasrat dan Kebutuhan:: Kontekstualisasi kata al-mulk dalam Al-Qur’an QS. Āli ‘Imrān (3): 26 - Bukhory, Umar; Mubarok, Ghozi (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
The year 2024 is a political year in Indonesia, with general elections. As a mandate to be fulfilled, becoming a leader, holding power, or holding public office has the potential to be disastrous for the region they govern if carried out by those lacking the necessary competence and skills. This article aims to explain the meaning and impact of power based on the interpretation of QS. Ali ‘Imran (3): 26. This study uses contextual analysis as part of the study of the Semantics of the Qur'an, because it assumes the relationship of certain texts with their historical and linguistic contexts, as well as a socio-textual approach, which connects the study of interpretation with the socio-political concept in the Islamic treasury. The conclusion of this study is that, based on its original meaning, power belongs to God universally and absolutely, and is also part of His will. As the owner of power, God grants and/or withdraws it from humans, based on all His goodness. Power can impact the humiliation and glory of those who exercise it, so they must exercise it with humility, full responsibility, and complete trust (faith) in its absolute owner. The contextualization of these three qualities gives rise to the nature of a leader as a servant of the society interests, just and wise, open to criticism, wise in making decisions based on the principle of deliberation, high integrity and accountability, and able to cooperate with others harmoniously.